UV-cured color-tunable dual-emission room temperature phosphorescent material as well as preparation method and application thereof

Through UV curing crosslinking technology, a color-tunable dual-emitting room temperature phosphorescent material was prepared. The combination of carbon quantum dots and cellulose-based derivatives was used to solve the problems of single luminescence color and unstable performance of existing materials, and the effect of emitting different colors of phosphorescence at room temperature was achieved, and the stability and application potential of the material were improved.

CN119592325AActive Publication Date: 2025-03-11WUHAN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411655772.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-11
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

The existing room temperature phosphorescent materials have single luminous color, which is difficult to achieve color regulation, and their performance is unstable during the actual preparation process.

Method used

UV-cured color-tunable dual-emission room temperature phosphorescent material is prepared by mixing carbon quantum dots, acrylamide and cellulose-based derivatives, heating and cross-linking and drying. The carbon quantum dots are used as the main phosphorescence color center, and the polyacrylamide and cellulose-based derivatives are double cross-linked as the substrate to achieve color tunability.

Benefits of technology

It realizes the characteristics of emitting phosphorescence in different colors at room temperature, the color is adjustable, and the material stability and service life are improved. It is suitable for anti-counterfeiting inks, optical information encoding and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592325A_ABST
    Figure CN119592325A_ABST
Patent Text Reader

Abstract

The invention provides a UV-cured color-tunable dual-emission room-temperature phosphorescent material as well as a preparation method and application thereof, and belongs to the technical field of color-tunable room-temperature phosphorescent functional materials. According to the invention, nitrogen-doped or nitrogen-metal ion-doped carbon quantum dots are used as a main ultraviolet light response phosphorescence color development center, a polyacrylamide and cellulose-based derivative double network is used as a substrate and a secondary phosphorescence color development center, acrylamide double bonds are broken into polyacrylamide through ultraviolet light, and further dehydration is carried out; the prepared room-temperature phosphorescent material shows different visible light colors under the excitation of ultraviolet light with two wavelengths, is tunable in color, can be applied to the fields of anti-forgery ink, optical information coding, photoelectric devices, advanced information encryption, humidity sensing detection and the like, and has wide application prospects. Wide popularization and application prospects are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of color-tunable room temperature phosphorescent functional materials, and in particular to a UV-cured color-tunable dual-emission room temperature phosphorescent material and a preparation method and application thereof. Background Art

[0002] Room temperature phosphorescent materials refer to materials that can continuously emit light at room temperature. Their working principle is through the storage and release of excited state energy. After being irradiated by an excitation light source (such as ultraviolet light or visible light), the material can absorb energy and continue to emit light for a period of time after the excitation light source is turned off. Room temperature phosphorescent materials usually have a long luminescence life and can emit light of different colors. They are widely used in lighting, display, sensors, safety signs and other fields.

[0003] Existing room temperature phosphorescent materials emit a single color and can only emit blue or green light after being excited. This is usually due to the energy level structure design of the material and the selection of doping elements. Existing materials often focus on luminescence efficiency and stability when designed, but there is relatively little research on color regulation. The existing strategy of achieving diversified phosphorescence colors under multiple excitations based on multi-component mixing requires the addition of multi-component mixing, and components emitting different colors may interfere with each other, resulting in unstable performance during the actual preparation process. In addition, the sensitivity of existing materials to excitation wavelengths also limits the range of their color changes. Therefore, finding a room temperature phosphorescent material with stable components, easy preparation and tunable color is of practical significance to the development and application of phosphorescent materials. Summary of the invention

[0004] In view of the above deficiencies in the prior art, the present invention provides a UV-curable, color-tunable dual-emission room temperature phosphorescent material and a preparation method and application thereof.

[0005] To achieve the above purpose, the specific technical solutions of the present invention are as follows:

[0006] In a first aspect, the present invention provides a UV-curable color-tunable dual-emission room temperature phosphorescent material, wherein raw materials including carbon quantum dots, acrylamide, and cellulose-based derivatives are mixed, heated, UV-cured, cross-linked, and dried to obtain the UV-curable color-tunable dual-emission room temperature phosphorescent material;

[0007] The carbon quantum dots are nitrogen-doped carbon quantum dots or nitrogen-metal ion-doped carbon quantum dots.

[0008] The UV-curable color-tunable dual-emission room temperature phosphorescent material of the present invention uses carbon quantum dots as the main phosphorescent color-emitting center and a double cross-linked network of polyacrylamide and cellulose-based derivatives as a substrate. At the same time, the cellulose-based derivative also serves as a secondary phosphorescent color-emitting center. The acrylamide is polymerized and cross-linked under the action of ultraviolet light, and further dehydrated to provide a rigid environment. At the same time, the cellulose-based derivative and the carbon quantum dots are combined under the action of strong hydrogen bonding sites and a cross-linking agent. The prepared room temperature phosphorescent material can emit phosphorescence of different colors at room temperature.

[0009] The UV-curable color-tunable dual-emission room temperature phosphorescent material provided by the present invention has the characteristics of dual-color photoluminescence under ultraviolet excitation and is color-tunable, including fluorescence and phosphorescence. The UV-curable color-tunable dual-emission room temperature phosphorescent material can emit blue fluorescence under the excitation of an ultraviolet light source with a wavelength of 254 nm, and emits a dark blue phosphorescent afterglow after the excitation stops. The fluorescence and phosphorescence emitted by the UV-curable color-tunable dual-emission room temperature phosphorescent material under the excitation of a 365 nm ultraviolet light source are mainly provided by carbon quantum dots, and the colors of the fluorescence and phosphorescence emitted are different due to different types or proportions of metal ions. Therefore, under the excitation of an ultraviolet light source with a wavelength of 365 nm, the UV-curable color-tunable dual-emission room temperature phosphorescent material can emit blue, green or orange-red fluorescence, and emit blue, green or orange-red phosphorescent afterglow after the excitation stops.

[0010] Specifically, the dual-emission room temperature phosphorescent material, when excited by an ultraviolet light source with a wavelength of 254 nm, has a fluorescence emission spectrum wavelength range of 375 to 550 nm, an emission peak at 416 nm, and exhibits deep blue fluorescence; about 3 seconds after the excitation stops, there is a blue phosphorescent afterglow visible to the naked eye, the phosphorescent emission spectrum wavelength range is 375 to 550 nm, and the emission peak appears at 426 nm;

[0011] The dual-emission room temperature phosphorescent material has a fluorescence emission spectrum wavelength range of 375-700 nm under the excitation of an ultraviolet light source with a wavelength of 275-365 nm. Affected by the carbon quantum dots doped with nitrogen-metal ions as the chromogenic center, the emission peak shows an excitation-dependent characteristic, the emission peak appears between 400-650 nm, the peak width is large, and the color varies with the type and proportion of the metal ions used for doping and the wavelength of the ultraviolet light source used for excitation, showing blue, green, orange-red, etc.; about 4-15 seconds after the excitation stops, there is a blue, green, orange-red, etc. phosphorescent afterglow visible to the naked eye; the phosphorescent emission spectrum wavelength range is 375-700 nm, the emission peak appears between 400-650 nm, and the phosphorescent lifetime in this excitation range is also affected by the type and proportion of the metal ions used for doping.

[0012] Furthermore, the phosphorescence color is regulated by changing the type and / or content of the metal ions doped in the carbon quantum dots, thereby achieving color tunability.

[0013] Furthermore, the cellulose-based derivative is one or more of cellulose nitrate, cellulose acetate, cellulose acetate butyrate, cellulose xanthate, methyl cellulose, carboxymethyl cellulose, ethyl cellulose, hydroxyethyl cellulose, cyanoethyl cellulose, hydroxypropyl cellulose and hydroxypropyl methyl cellulose.

[0014] The present invention uses nitrogen-doped carbon quantum dots or nitrogen-metal ion-doped carbon quantum dots as the main phosphorescent color center and adds them to acrylamide and cellulose-based derivative precursor solutions. The carbon quantum dots themselves have the characteristics of photoluminescence, and nitrogen doping can reduce the intersystem crossing energy difference, thereby effectively activating the triplet state, promoting the occurrence of the intersystem crossing process, and improving the fluorescence quantum yield and fluorescence emission intensity of its photoluminescence characteristics, while metal ion doping affects the core structure of the carbon quantum dots, reduces the energy band gap, and the smaller the energy required for excitation, the wavelength of the emitted light will be red-shifted, and at the same time, the incorporation of metal ions changes the size of the carbon quantum dots, resulting in changes in the emission wavelength and spectrum width of its photoluminescence, thereby achieving the tunability of the emission color of the dual-emission room temperature phosphorescent material provided by the present invention. During the photoinitiated free radical polymerization process in the above-mentioned acrylamide and cellulose-based derivative precursor solutions, the carbon quantum dots are interspersed between the molecular chains of polyacrylamide and cellulose-based derivatives. Similar to the binding mode of the secondary phosphorescent chromophore center, the abundant carboxyl, amino, hydroxyl and other functional groups on the surface of the carbon quantum dots form hydrogen bonds and van der Waals forces under the joint attraction of the strong hydrogen bonding sites on the cross-linking agent and the matrix molecular chain. The rigid microenvironment formed after complete curing further enhances the fixation effect of the carbon quantum dots, so that the fluorescent carbon quantum dots as the main phosphorescent chromophore center give the material system the characteristics of phosphorescent emission and are mainly involved in the regulation of phosphorescent color. In addition, the spatial conjugation in the tightly packed double cross-linked network increases the degree of electron delocalization, making it easier for electrons to enter the excited state. The phosphorescence emission of carbon quantum dots as the main phosphorescent color center under ultraviolet light is red-shifted compared to the fluorescence emission when it is a single component. After the ultraviolet light excitation in the range of 275 to 365 nm stops, there is a phosphorescence afterglow visible to the naked eye for about 4 to 15 s. The phosphorescence color and lifetime are affected by the type and content of metal ions used for doping, and exhibit excitation-dependent characteristics, that is, the emission wavelength changes with the change of the excitation wavelength.

[0015] The present invention uses acrylamide and cellulose-based derivatives as precursor solutions of the main matrix, adds a photoinitiator and a crosslinking agent, and free radicals of the photoinitiator are released under the action of UV, attacking unsaturated double bonds in acrylamide monomers and crosslinking agents, initiating free radical polymerization of acrylamide monomers to form polyacrylamide. At the same time, under the action of the crosslinking agent and abundant strong hydrogen bonding sites such as carboxyl groups and amino groups, highly complex interchain entanglement occurs with the cellulose-based derivative to form a three-dimensional network structure. After complete solidification, the tightly packed double crosslinked network increases the degree of spatial conjugation, and the cellulose-based derivative is more tightly restricted, further avoiding unnecessary non-radiative transitions and quenching, so that the cellulose-based derivative having fluorescence emission itself exhibits phosphorescent emission, and plays the role of a secondary phosphorescent color center in the material matrix system of the present invention, which is specifically manifested as blue phosphorescence visible to the naked eye for about 3 seconds after the 254 nm ultraviolet light excitation stops.

[0016] Furthermore, the method for preparing carbon quantum dots comprises the following steps:

[0017] (1) Ethylenediaminetetraacetic acid disodium salt and metal salt are mixed evenly in water, heated at 50-95°C until the water is completely volatilized, and then transferred to 60-90°C for further drying to obtain a precursor powder;

[0018] (2) reacting the precursor powder at 200-400 °C to obtain a reaction product;

[0019] (3) Dissolving the reaction product and mixing it evenly with an organic solvent, filtering it, and drying the filtrate to obtain carbon quantum dot powder.

[0020] Furthermore, the molar ratio of the disodium salt of ethylenediaminetetraacetic acid to the metal salt is 10:(0-10); when the amount of the metal salt is 0, nitrogen-doped carbon quantum dots are prepared.

[0021] Furthermore, the disodium salt of ethylenediaminetetraacetic acid includes a hydrate and / or a non-hydrate of the disodium salt of ethylenediaminetetraacetic acid.

[0022] Furthermore, the metal salt is selected from one or more of chloride salts of magnesium, calcium, manganese, iron, ferrous iron, cobalt, nickel, copper, zinc ions and hydrates of chloride salts.

[0023] Furthermore, the organic solvent is ethanol.

[0024] Specifically, the preparation method of the carbon quantum dots is as follows: disodium ethylenediaminetetraacetic acid and a metal salt are mixed in proportion, dissolved in deionized water, stirred and heated at 50-95°C in an open container until the water is completely volatilized, and transferred to an oven for further drying at 60-90°C to obtain a precursor powder; the precursor powder is reacted at 200-400°C with nitrogen for 1-20 min to obtain a reaction product; the reaction product is dissolved in ethanol and then ultrasonically treated for 10-40 min, filtered with a 0.22 μm filter membrane, and the filtrate is dried to obtain a carbon quantum dot powder.

[0025] In a second aspect, the present invention provides a method for preparing a UV-curable color-tunable dual-emission room temperature phosphorescent material, comprising the following steps:

[0026] S1. Add acrylamide, cellulose-based derivatives, photoinitiator, and crosslinking agent to an aqueous solution of carbon quantum dots, and heat to 60-90° C. to obtain a color-tunable dual-emission room temperature phosphorescent material precursor solution;

[0027] S2. Curing the color-tunable dual-emission room temperature phosphorescent material precursor solution under UV until the precursor solution becomes a non-sticky, non-flowing solid, and drying until the moisture in the solid completely disappears and becomes a hard solid, thereby obtaining a UV-cured color-tunable dual-emission room temperature phosphorescent material.

[0028] Furthermore, in step S1, the heating temperature is 65°C.

[0029] Furthermore, in step S1, the concentration of the aqueous solution of carbon quantum dots is 50-1000 μg / mL.

[0030] Furthermore, the concentration of the carbon quantum dot solution is 850 μg / mL.

[0031] Furthermore, in step S1, the mass ratio of acrylamide, cellulose-based derivative, photoinitiator and cross-linking agent is 100:(0.01~3):(0.1~1):(0.01~1).

[0032] Furthermore, the mass ratio of the acrylamide, the cellulose-based derivative, the photoinitiator and the cross-linking agent is 100:1.515:0.5:0.1.

[0033] Furthermore, in step S1, the mass ratio of acrylamide to carbon quantum dots is 3000:(0.5~10).

[0034] Furthermore, in step S1, the photoinitiator is one or more of 2,4-dihydroxybenzophenone, 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexylphenyl ketone, and diphenylacetone.

[0035] Furthermore, in step S1, the cross-linking agent is one or more of divinylbenzene, diisocyanate, N,N-methylenebisacrylamide, and ethylenediamine.

[0036] Furthermore, in step S2, the curing power and time are selected according to the amount of material to be prepared.

[0037] Furthermore, in step S2, the drying is continuously performed under UV, or in an oven at 50-90°C.

[0038] Furthermore, in step S2, the drying is performed in an oven at 60°C; final curing by oven is more efficient than UV final curing, and the temperature of 60°C can take into account both moisture drying and protection of the phosphorescent color center from being destroyed.

[0039] In a third aspect, the present invention provides an application of the UV-cured color-tunable dual-emission room temperature phosphorescent material or the UV-cured color-tunable dual-emission room temperature phosphorescent material prepared by the method, and uses the UV-cured color-tunable dual-emission room temperature phosphorescent material as anti-counterfeiting ink, characteristic luminescent material for optical information encoding, surface color material for optoelectronic devices, advanced intelligent coating material for advanced information encryption, raw material for phosphorescent objects and appliances, or humidity sensitive element for humidity sensing detection device.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] (1) The present invention provides a UV-curable, color-tunable dual-emission room-temperature phosphorescent material, which uses a double cross-linked network of polyacrylamide and a cellulose-based derivative as a substrate, so that carbon quantum dots with excellent water solubility and photoluminescence properties can be evenly and effectively dispersed in the substrate, avoiding their re-aggregation and sedimentation, thereby improving the stability and service life of the phosphorescent material. The cellulose-based derivative as a substrate component also acts as a secondary phosphorescent color center, providing a stable phosphorescent emission characteristic site for the phosphorescent material. In addition, the spatial conjugation in the tightly packed double cross-linked network increases the degree of electron delocalization, making it easier for electrons to enter the excited state, promoting the efficiency of crossing between the singlet state and the triplet state system, improving the phosphorescence lifetime, and inhibiting non-radiative transitions through the rigid microenvironment provided by hydrogen bonds and van der Waals forces. Under the combined effect, the phosphorescence effect is enhanced.

[0042] (2) The UV-curable color-tunable dual-emission room-temperature phosphorescent material provided by the present invention uses carbon quantum dots as the main phosphorescent color-emitting center, has high brightness, low raw material cost, simple preparation steps, and does not require tedious purification process, which is conducive to large-scale production; the luminescent color can be regulated by controlling the feed ratio and the type of metal ions, and has the function of color tunability.

[0043] (3) The present invention provides a UV-curable color-tunable dual-emission room-temperature phosphorescent material, in which one chromophore center can provide stable excitation-emission fixed corresponding blue fluorescence and phosphorescence, and the other chromophore center exhibits excitation-dependent characteristics and can emit fluorescence and phosphorescence of different colors under the excitation of ultraviolet light sources of different wavelengths. The fluorescence and phosphorescence colors of the two chromophore centers are different, and there are differences in the phosphorescence lifespans. Mixed-color emission can be achieved at the intersection of the excitation wavelengths, thereby constructing colorful photoluminescence characteristics.

[0044] (4) The UV-curable color-tunable dual-emission room temperature phosphorescent material provided by the present invention has the characteristic of water quenching. The photoluminescence phenomenon disappears after contact with water, and the photoluminescence characteristics are restored after the water is dried. The UV-curable color-tunable dual-emission room temperature phosphorescent material provided by the present invention can be used as anti-counterfeiting ink, characteristic luminescent material for optical information encoding, advanced intelligent coating material for advanced information encryption, raw materials for phosphorescent objects and appliances, and the UV-curable color-tunable dual-emission room temperature phosphorescent material can also be used as the surface color material of optoelectronic devices and the humidity sensitive element of humidity sensing detection device. The preparation method of the material in the present invention is in the form of a precursor solution, which has broad promotion and application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is a high-resolution transmission electron microscopy image of nitrogen-metal ion-doped carbon quantum dots prepared in Example 1 of the present invention;

[0046] Figure 2 This is a three-dimensional fluorescence spectrum of the nitrogen-metal ion-doped carbon quantum dot solution prepared in Example 1 of the present invention at room temperature;

[0047] Figure 3 Normalized fluorescence emission spectra of the carbon quantum dot solution prepared by changing the ratio of copper chloride under room temperature and excitation by a 365 nm wavelength ultraviolet light source;

[0048] Figure 4 The three-dimensional phosphorescence spectrum of the UV-curable color-tunable dual-emission room temperature phosphorescent material prepared in Example 1 of the present invention at room temperature;

[0049] Figure 5 The phosphorescence emission spectra of the UV-curable color-tunable dual-emission room temperature phosphorescent material prepared in Example 1 of the present invention under room temperature conditions under the excitation of ultraviolet light sources with wavelengths of 254, 310, 315 and 365 nm, respectively, and the corresponding phosphorescence emission peaks appear at 426, 515, 527 and 540 nm, respectively;

[0050] Figure 6This is a phosphorescence lifetime diagram of the UV-curable color-tunable dual-emission room temperature phosphorescent material prepared in Example 1 of the present invention under the excitation of a 254nm wavelength ultraviolet light source;

[0051] Figure 7 This is a phosphorescence lifetime diagram of the UV-curable color-tunable dual-emission room temperature phosphorescent material prepared in Example 1 of the present invention under excitation by a 310 nm wavelength ultraviolet light source;

[0052] Figure 8 This is a phosphorescence lifetime diagram of the UV-curable color-tunable dual-emission room temperature phosphorescent material prepared in Example 1 of the present invention under excitation by a 315 nm wavelength ultraviolet light source;

[0053] Fig. 9 This is a phosphorescence lifetime diagram of the UV-curable color-tunable dual-emission room temperature phosphorescent material prepared in Example 1 of the present invention under excitation by a 365nm wavelength ultraviolet light source. DETAILED DESCRIPTION

[0054] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0055] The present invention provides a UV-curable color-tunable dual-emission room temperature phosphorescent material, which comprises mixing raw materials including carbon quantum dots, acrylamide, and cellulose-based derivatives, heating, UV-curing cross-linking, and drying to obtain the UV-curable color-tunable dual-emission room temperature phosphorescent material;

[0056] The carbon quantum dots are nitrogen-doped carbon quantum dots or nitrogen-metal ion-doped carbon quantum dots.

[0057] In some examples, the cellulose-based derivative is one or more of cellulose nitrate, cellulose acetate, cellulose acetate butyrate, cellulose xanthate, methyl cellulose, carboxymethyl cellulose, ethyl cellulose, hydroxyethyl cellulose, cyanoethyl cellulose, hydroxypropyl cellulose, and hydroxypropyl methyl cellulose.

[0058] The method for preparing carbon quantum dots comprises the following steps:

[0059] (1) Ethylenediaminetetraacetic acid disodium salt and metal salt are mixed evenly in water, heated at 50-95°C until the water is completely volatilized, and then transferred to 60-90°C for further drying to obtain a precursor powder;

[0060] (2) reacting the precursor powder at 200-400 °C to obtain a reaction product;

[0061] (3) Dissolving the reaction product and mixing it evenly with an organic solvent, filtering it, and drying the filtrate to obtain carbon quantum dot powder.

[0062] In some examples, the molar ratio of the disodium salt of ethylenediaminetetraacetic acid to the metal salt is 10:(0-10); when the amount of the metal salt is 0, nitrogen-doped carbon quantum dots are prepared.

[0063] In some examples, the disodium salt of ethylenediaminetetraacetic acid includes a hydrate and / or a non-hydrate of disodium salt of ethylenediaminetetraacetic acid.

[0064] In some examples, the metal salt is selected from one or more of chloride salts and hydrates of chloride salts of magnesium, calcium, manganese, iron, ferrous iron, cobalt, nickel, copper, and zinc ions.

[0065] The method for preparing the UV-curable color-tunable dual-emission room temperature phosphorescent material comprises the following steps:

[0066] S1. Add acrylamide, cellulose-based derivatives, photoinitiator, and crosslinking agent to an aqueous solution of carbon quantum dots, and heat to 60-90° C. to obtain a color-tunable dual-emission room temperature phosphorescent material precursor solution;

[0067] S2. Curing the color-tunable dual-emission room temperature phosphorescent material precursor solution under UV until the precursor solution becomes a non-sticky, non-flowing solid, and drying until the moisture in the solid completely disappears and becomes a hard solid, thereby obtaining a UV-cured color-tunable dual-emission room temperature phosphorescent material.

[0068] In some examples, in step S1, the concentration of the aqueous solution of carbon quantum dots is 50-1000 μg / mL.

[0069] In some examples, in step S1, the mass ratio of acrylamide, cellulose-based derivative, photoinitiator, and cross-linking agent is 100: (0.01~3): (0.1~1): (0.01~1).

[0070] In some examples, in step S1, the mass ratio of acrylamide to carbon quantum dots is 3000:(0.5~10).

[0071] In some examples, in step S1, the photoinitiator is one or more of 2,4-dihydroxybenzophenone, 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexylphenyl ketone, and diphenylacetone.

[0072] In some examples, in step S1, the cross-linking agent is one or more of divinylbenzene, diisocyanate, N,N-methylenebisacrylamide, and ethylenediamine.

[0073] In some examples, in step S2, the drying is continuously performed under UV, or in an oven at 50-90°C.

[0074] Example 1

[0075] A UV-curable color-tunable dual-emission room temperature phosphorescent material, the preparation steps are as follows:

[0076] (1) Preparation of nitrogen-metal ion doped carbon quantum dots:

[0077] Weigh 3 g of disodium ethylenediaminetetraacetic acid and 1.196 g of copper chloride, dissolve in 30 mL of deionized water, heat and stir in an open container at 60 °C, during which water evaporates, add deionized water along the inner wall of the container appropriately, and redissolve the solute precipitated on the inner wall of the container due to drying until the water is completely evaporated, and then transfer to a 60 °C oven for further drying to obtain a precursor powder; place the precursor powder in a nitrogen atmosphere, heat to 300 °C and keep for 5 min, grind into fine powder after natural cooling, add 30 mL of anhydrous ethanol and ultrasonically treat for 30 min, then filter with a 0.22 μm filter membrane, and dry the filtrate to obtain nitrogen-copper ion-doped carbon quantum dot powder;

[0078] (2) Preparation of color-tunable dual-emission room temperature phosphorescent material precursor solution:

[0079] The carbon quantum dots obtained in step (1) are prepared into 10 mL of an aqueous solution of 800 μg / mL, 3 g of acrylamide, 0.03 g of carboxymethyl cellulose, 0.027 g of 1-hydroxycyclohexyl phenyl ketone and 0.008 g of N,N-methylenebisacrylamide are added thereto, and the mixture is heated and stirred at 60°C until dissolved to obtain a color-tunable dual-emission room temperature phosphorescent material precursor solution;

[0080] (3) Preparation of dual-emission room temperature phosphorescent materials:

[0081] The color-tunable dual-emission room temperature phosphorescent material precursor solution obtained in step (2) was transferred to a transparent plastic culture dish with a diameter of 60 mm so that the solution evenly spread the bottom of the culture dish. It was irradiated with a UV curing lamp with a power of 30 W for 20 seconds to obtain a non-flowing solid, completing polymerization and cross-linking. It was then transferred to an oven at 60°C for heating and drying for 6 hours to become a hard solid, thereby obtaining a UV-cured color-tunable dual-emission room temperature phosphorescent material.

[0082] Example 2

[0083] A UV-curable color-tunable dual-emission room temperature phosphorescent material, the preparation steps are as follows:

[0084] (1) Preparation of nitrogen-doped carbon quantum dots:

[0085] Weigh 3 g of disodium ethylenediaminetetraacetic acid, dissolve it in 30 mL of deionized water, heat and stir it in an open container at 60 °C, during which the water evaporates, add deionized water along the inner wall of the container appropriately, and redissolve the solute precipitated and hanging on the inner wall of the container due to drying until the water evaporates completely, and then transfer it to a 60 °C oven for further drying to obtain a precursor powder; place the precursor powder in a nitrogen atmosphere, heat it to 300 °C and keep it for 5 min, grind it into fine powder after cooling naturally, add 30 mL of anhydrous ethanol and ultrasonically treat it for 30 min, then filter it with a 0.22 μm filter membrane, and dry the filtrate to obtain nitrogen-doped carbon quantum dot powder;

[0086] (2) Preparation of color-tunable dual-emission room temperature phosphorescent material precursor solution:

[0087] The carbon quantum dots obtained in step (1) are prepared into 10 mL of an aqueous solution of 800 μg / mL, 3 g of acrylamide, 0.03 g of carboxymethyl cellulose, 0.027 g of 1-hydroxycyclohexyl phenyl ketone and 0.008 g of N,N-methylenebisacrylamide are added thereto, and the mixture is heated and stirred at 60°C until dissolved to obtain a color-tunable dual-emission room temperature phosphorescent material precursor solution;

[0088] (3) Preparation of dual-emission room temperature phosphorescent materials:

[0089] The color-tunable dual-emission room temperature phosphorescent material precursor solution obtained in step (2) was transferred to a transparent plastic culture dish with a diameter of 60 mm so that the solution evenly spread the bottom of the culture dish. It was irradiated with a UV curing lamp with a power of 30 W for 20 seconds to obtain a non-flowing solid, completing polymerization and cross-linking. It was then transferred to an oven at 60°C for heating and drying for 6 hours to become a hard solid, thereby obtaining a UV-cured color-tunable dual-emission room temperature phosphorescent material.

[0090] Example 3

[0091] A UV-curable color-tunable dual-emission room temperature phosphorescent material, the preparation steps are as follows:

[0092] (1) Preparation of nitrogen-metal ion doped carbon quantum dots:

[0093] Weigh 3 g of disodium ethylenediaminetetraacetic acid and 0.598 g of copper chloride, dissolve in 30 mL of deionized water, heat and stir in an open container at 60 °C, during which water evaporates, add deionized water along the inner wall of the container appropriately, and redissolve the solute precipitated and hanging on the inner wall of the container due to drying until the water is completely evaporated, and then transfer to a 60 °C oven for further drying to obtain a precursor powder; place the precursor powder in a nitrogen atmosphere, heat to 300 °C and keep for 5 min, grind into fine powder after natural cooling, add 30 mL of anhydrous ethanol and ultrasonically treat for 30 min, then filter with a 0.22 μm filter membrane, and dry the filtrate to obtain nitrogen-copper ion-doped carbon quantum dot powder;

[0094] (2) Preparation of color-tunable dual-emission room temperature phosphorescent material precursor solution:

[0095] The carbon quantum dots obtained in step (1) are prepared into 10 mL of an aqueous solution of 800 μg / mL, 3 g of acrylamide, 0.03 g of carboxymethyl cellulose, 0.027 g of 1-hydroxycyclohexyl phenyl ketone and 0.008 g of N,N-methylenebisacrylamide are added thereto, and the mixture is heated and stirred at 60°C until dissolved to obtain a color-tunable dual-emission room temperature phosphorescent material precursor solution;

[0096] (3) Preparation of dual-emission room temperature phosphorescent materials:

[0097] The color tunable dual-emission room temperature phosphorescent material precursor solution prepared in step (2) was transferred to a transparent plastic culture dish with a diameter of 60 mm, so that the solution evenly spread the bottom of the culture dish, and irradiated with a UV curing lamp with a power of 30 W for 20 seconds to obtain a non-flowing solid, completing the polymerization and cross-linking, and then transferred to a 60°C oven for heating and drying for 6 hours to become a hard solid, thereby obtaining a UV-cured color tunable dual-emission room temperature phosphorescent material.

[0098] Example 4

[0099] A UV-curable color-tunable dual-emission room temperature phosphorescent material, the preparation steps are as follows:

[0100] (1) Preparation of nitrogen-metal ion doped carbon quantum dots:

[0101] Weigh 3 g of disodium ethylenediaminetetraacetic acid and 0.897 g of copper chloride, dissolve in 30 mL of deionized water, heat and stir in an open container at 60 °C, during which water evaporates, add deionized water along the inner wall of the container appropriately, and redissolve the solute precipitated on the inner wall of the container due to drying until the water is completely evaporated, and then transfer to a 60 °C oven for further drying to obtain a precursor powder; place the precursor powder in a nitrogen atmosphere, heat to 300 °C and keep for 5 min, grind into fine powder after natural cooling, add 30 mL of anhydrous ethanol and ultrasonically treat for 30 min, then filter with a 0.22 μm filter membrane, and dry the filtrate to obtain nitrogen-copper ion-doped carbon quantum dot powder;

[0102] (2) Preparation of color-tunable dual-emission room temperature phosphorescent material precursor solution:

[0103] The carbon quantum dots obtained in step (1) are prepared into 10 mL of an aqueous solution of 800 μg / mL, 3 g of acrylamide, 0.03 g of carboxymethyl cellulose, 0.027 g of 1-hydroxycyclohexyl phenyl ketone and 0.008 g of N,N-methylenebisacrylamide are added thereto, and the mixture is heated and stirred at 60°C until dissolved to obtain a color-tunable dual-emission room temperature phosphorescent material precursor solution;

[0104] (3) Preparation of dual-emission room temperature phosphorescent materials:

[0105] The color-tunable dual-emission room temperature phosphorescent material precursor solution obtained in step (2) was transferred to a transparent plastic culture dish with a diameter of 60 mm so that the solution evenly spread the bottom of the culture dish. It was irradiated with a UV curing lamp with a power of 30 W for 20 seconds to obtain a non-flowing solid, completing polymerization and cross-linking. It was then transferred to an oven at 60°C for heating and drying for 6 hours to become a hard solid, thereby obtaining a UV-cured color-tunable dual-emission room temperature phosphorescent material.

[0106] Example 5

[0107] A UV-curable color-tunable dual-emission room temperature phosphorescent material, the preparation steps are as follows:

[0108] (1) Preparation of nitrogen and metal ion doped carbon quantum dots:

[0109] Weigh 3 g of disodium ethylenediaminetetraacetic acid and 0.299 g of copper chloride, dissolve in 30 mL of deionized water, heat and stir in an open container at 60 ° C, during which water evaporates, add deionized water along the inner wall of the container appropriately, and redissolve the solute precipitated on the inner wall of the container due to drying until the water is completely evaporated, and then transfer to a 60 ° C oven for further drying to obtain a precursor powder; place the precursor powder in a nitrogen atmosphere, heat to 300 ° C and keep for 5 min, grind into fine powder after natural cooling, add 30 mL of anhydrous ethanol and ultrasonically treat for 30 min, then filter with a 0.22 μm filter membrane, and dry the filtrate to obtain nitrogen-copper ion-doped carbon quantum dot powder;

[0110] (2) Preparation of color-tunable dual-emission room temperature phosphorescent material precursor solution:

[0111] The carbon quantum dots obtained in step (1) are prepared into 10 mL of an aqueous solution of 800 μg / mL, 3 g of acrylamide, 0.03 g of carboxymethyl cellulose, 0.027 g of 1-hydroxycyclohexyl phenyl ketone and 0.008 g of N,N-methylenebisacrylamide are added thereto, and the mixture is heated and stirred at 60°C until dissolved to obtain a color-tunable dual-emission room temperature phosphorescent material precursor solution;

[0112] (3) Preparation of dual-emission room temperature phosphorescent materials:

[0113] The color-tunable dual-emission room temperature phosphorescent material precursor solution obtained in step (2) was transferred to a transparent plastic culture dish with a diameter of 60 mm so that the solution evenly spread the bottom of the culture dish. It was irradiated with a UV curing lamp with a power of 30 W for 20 seconds to obtain a non-flowing solid, completing polymerization and cross-linking. It was then transferred to an oven at 60°C for heating and drying for 6 hours to become a hard solid, thereby obtaining a UV-cured color-tunable dual-emission room temperature phosphorescent material.

[0114] Example 6

[0115] A UV-curable color-tunable dual-emission room temperature phosphorescent material, the preparation steps are as follows:

[0116] (1) Preparation of nitrogen and metal ion doped carbon quantum dots:

[0117] Weigh 3 g of disodium ethylenediaminetetraacetic acid and 1.214 g of zinc chloride, dissolve in 30 mL of deionized water, heat and stir in an open container at 60 °C, during which water evaporates, add deionized water along the inner wall of the container appropriately, and redissolve the solute precipitated on the inner wall of the container due to drying until the water is completely evaporated, and then transfer to a 60 °C oven for further drying to obtain a precursor powder; place the precursor powder in a nitrogen atmosphere, heat to 300 °C and keep for 5 min, grind into fine powder after natural cooling, add 30 mL of anhydrous ethanol and ultrasonically treat for 30 min, then filter with a 0.22 μm filter membrane, and dry the filtrate to obtain nitrogen-zinc ion-doped carbon quantum dot powder;

[0118] (2) Preparation of color-tunable dual-emission room temperature phosphorescent material precursor solution:

[0119] The carbon quantum dots obtained in step (1) are prepared into 10 mL of an aqueous solution of 800 μg / mL, 3 g of acrylamide, 0.03 g of carboxymethyl cellulose, 0.027 g of 1-hydroxycyclohexyl phenyl ketone and 0.008 g of N,N-methylenebisacrylamide are added thereto, and the mixture is heated and stirred at 60°C until dissolved to obtain a color-tunable dual-emission room temperature phosphorescent material precursor solution;

[0120] (3) Preparation of dual-emission room temperature phosphorescent materials:

[0121] The color-tunable dual-emission room temperature phosphorescent material precursor solution obtained in step (2) was transferred to a transparent plastic culture dish with a diameter of 60 mm so that the solution evenly spread the bottom of the culture dish. It was irradiated with a UV curing lamp with a power of 30 W for 20 seconds to obtain a non-flowing solid, completing polymerization and cross-linking. It was then transferred to an oven at 60°C for heating and drying for 6 hours to become a hard solid, thereby obtaining a UV-cured color-tunable dual-emission room temperature phosphorescent material.

[0122] Example 7

[0123] A UV-curable color-tunable dual-emission room temperature phosphorescent material, the preparation steps are as follows:

[0124] (1) Preparation of nitrogen and metal ion doped carbon quantum dots:

[0125] Weigh 3 g of disodium ethylenediaminetetraacetic acid and 1.196 g of copper chloride, dissolve in 30 mL of deionized water, heat and stir in an open container at 60 °C, during which water evaporates, add deionized water along the inner wall of the container appropriately, and redissolve the solute precipitated on the inner wall of the container due to drying until the water is completely evaporated, and then transfer to a 60 °C oven for further drying to obtain a precursor powder; place the precursor powder in a nitrogen atmosphere, heat to 300 °C and keep for 5 min, grind into fine powder after natural cooling, add 30 mL of anhydrous ethanol and ultrasonically treat for 30 min, then filter with a 0.22 μm filter membrane, and dry the filtrate to obtain nitrogen-copper ion-doped carbon quantum dot powder;

[0126] (2) Preparation of color-tunable dual-emission room temperature phosphorescent material precursor solution:

[0127] The carbon quantum dots obtained in step (1) are prepared into 10 mL of a 700 μg / mL aqueous solution, 3 g of acrylamide, 0.027 g of hydroxyethyl cellulose, 0.024 g of diphenylacetone and 0.01 g of ethylenediamine are added thereto, and the mixture is heated and stirred at 60°C until dissolved to obtain a color-tunable dual-emission room temperature phosphorescent material precursor solution;

[0128] (3) Preparation of dual-emission room temperature phosphorescent materials:

[0129] The color-tunable dual-emission room temperature phosphorescent material precursor solution obtained in step (2) was transferred to a transparent plastic culture dish with a diameter of 60 mm so that the solution evenly spread the bottom of the culture dish. It was irradiated with a UV curing lamp with a power of 20 W for 30 seconds to obtain a non-flowing solid, completing polymerization and cross-linking. It was then transferred to an oven at 60°C and heated and dried for 6 hours to become a hard solid, thereby obtaining a UV-cured color-tunable dual-emission room temperature phosphorescent material.

[0130] Example 8

[0131] A UV-curable color-tunable dual-emission room temperature phosphorescent material, the preparation steps are as follows:

[0132] (1) Preparation of nitrogen and metal ion doped carbon quantum dots:

[0133] Weigh 3 g of disodium ethylenediaminetetraacetic acid, 0.598 g of copper chloride and 0.607 g of zinc chloride, dissolve in 30 mL of deionized water, heat and stir in an open container at 60 ° C, during which water evaporates, add deionized water along the inner wall of the container appropriately, and redissolve the solute precipitated on the inner wall of the container due to drying until the water is completely evaporated, transfer to a 60 ° C oven for further drying to obtain a precursor powder, and then place the obtained precursor powder in a nitrogen atmosphere, heat to 300 ° C and keep for 5 min, grind into fine powder after natural cooling, add 30 mL of anhydrous ethanol and ultrasonically treat for 30 min, then filter with a 0.22 μm filter membrane, and take the filtrate and dry to obtain nitrogen-copper / zinc ion-doped carbon quantum dot powder;

[0134] (2) Preparation of color-tunable dual-emission room temperature phosphorescent material precursor solution:

[0135] The carbon quantum dots obtained in step (1) are prepared into 10 mL of an aqueous solution of 800 μg / mL, 3 g of acrylamide, 0.03 g of carboxymethyl cellulose, 0.027 g of 1-hydroxycyclohexyl phenyl ketone and 0.008 g of N,N-methylenebisacrylamide are added thereto, and the mixture is heated and stirred at 60°C until dissolved to obtain a color-tunable dual-emission room temperature phosphorescent material precursor solution;

[0136] (3) Preparation of dual-emission room temperature phosphorescent materials:

[0137] The color-tunable dual-emission room temperature phosphorescent material precursor solution obtained in step (2) was transferred to a transparent plastic culture dish with a diameter of 60 mm so that the solution evenly spread the bottom of the culture dish. It was irradiated with a UV curing lamp with a power of 30 W for 20 seconds to obtain a non-flowing solid, completing polymerization and cross-linking. It was then transferred to an oven at 60°C for heating and drying for 6 hours to become a hard solid, thereby obtaining a UV-cured color-tunable dual-emission room temperature phosphorescent material.

[0138] Figure 1 This is a high-resolution transmission electron microscopy image of the nitrogen-metal ion-doped carbon quantum dots prepared in Example 1; Figure 2 The three-dimensional fluorescence spectrum of the nitrogen-metal ion-doped carbon quantum dot solution prepared in Example 1 at room temperature; Figure 3 Normalized fluorescence emission spectra of nitrogen-metal ion-doped carbon quantum dot solutions prepared by changing the copper chloride ratio under room temperature and excitation by a 365 nm ultraviolet light source; the figure shows that the red shift phenomenon is obvious as the copper chloride ratio increases.

[0139] Figure 4 The three-dimensional phosphorescence spectrum of the UV-curable color-tunable dual-emission room temperature phosphorescent material prepared in Example 1 at room temperature; Figure 5The phosphorescence emission spectra of the UV-curable color-tunable dual-emission room temperature phosphorescent material prepared in Example 1 under room temperature conditions under the excitation of ultraviolet light sources with wavelengths of 254, 310, 315 and 365 nm, respectively, and the corresponding phosphorescence emission peaks appear at 426, 515, 527 and 540 nm, respectively; Figure 6 This is a phosphorescence lifetime diagram of the UV-curable color-tunable dual-emission room temperature phosphorescent material prepared in Example 1 under excitation by a 254 nm wavelength ultraviolet light source; Figure 7 This is a phosphorescence lifetime diagram of the UV-curable color-tunable dual-emission room temperature phosphorescent material prepared in Example 1 under excitation by a 310 nm wavelength ultraviolet light source; Figure 8 This is a phosphorescence lifetime diagram of the UV-curable color-tunable dual-emission room temperature phosphorescent material prepared in Example 1 under excitation by a 315 nm wavelength ultraviolet light source; Fig. 9 This is a phosphorescence lifetime diagram of the UV-curable color-tunable dual-emission room temperature phosphorescent material prepared in Example 1 under excitation by a 365nm wavelength ultraviolet light source.

[0140] According to experimental tests conducted by the inventors, the UV-curable color-tunable dual-emission room temperature phosphorescent materials prepared in Examples 2 to 8 also show different visible light colors under the excitation of two wavelengths of ultraviolet light, and the colors are tunable.

[0141] The present invention uses disodium ethylenediaminetetraacetic acid to prepare carbon quantum dots because it contains a rich nitrogen source, and disodium ethylenediaminetetraacetic acid, as a sodium salt, has better solubility than ethylenediaminetetraacetic acid; the inventors have found that compared with nitrogen-doped carbon quantum dots, carbon quantum dots that have not been doped with nitrogen have weaker photoluminescence intensity. In the preparation process of carbon quantum dots of the present invention, the precursor powder needs to be placed in an inert atmosphere for heating; after high-temperature heating in an inert atmosphere, the sodium salt will exist in the form of sodium carbonate, and when chloride salts of other types of metal ions are added, the sodium element will also exist in the form of sodium chloride. The present invention uses anhydrous ethanol as an extracting solution to avoid the extraction of sodium salt and minimize the influence of the sodium element. The inventors have found that the presence of sodium has the following effects: sodium salt will precipitate from the solution to form crystals, and in this process, smaller carbon quantum dots will be coated. If the carbon quantum dots coated with sodium salt are used to prepare UV-curable color-tunable dual-emission room-temperature phosphorescent materials, during the UV curing and subsequent drying stages, the sodium salt will precipitate and will co-precipitate with the carbon quantum dots, destroying the main phosphorescent color center and causing the performance of the room-temperature phosphorescent material to deteriorate.

[0142] In addition, the content and type of metal ions will affect the luminescent wavelength range of carbon quantum dots. The inventors have found that the heavier the metal ions are and the more they are added, the more red-shifted the luminescent color of the prepared carbon quantum dots will be, that is, the luminescence moves more and more toward red (e.g. Figure 3 As shown in Figure 2, when the content of copper ions increases, the emission wavelength of carbon quantum dots will redshift). However, sodium has a small atomic size and relative atomic mass, and a weak heavy atom effect, which has little effect on the size of carbon quantum dots and the π-π stacking effect in the carbon core. Therefore, it is difficult to use sodium to regulate the emission color of room temperature phosphorescent materials.

[0143] The present invention uses cellulose-based derivatives as secondary phosphorescent color centers. One of the reasons why they can emit light is that the amount added is small. The inventors have found that when the amount of cellulose-based derivatives added is too large, the phosphorescence and fluorescence brightness of the material will be reduced; and when the amount of cellulose-based derivatives added is too large, cellulose such as carboxymethyl cellulose and ethyl cellulose is difficult to completely dissolve when preparing the precursor solution, resulting in the prepared room temperature phosphorescent material having a weak photoluminescence intensity. In the process of preparing the room temperature phosphorescent material from the precursor solution, the precursor solution needs to be further dried after UV curing until the water in the solid completely disappears and becomes a hard solid. The inventors have found that the residual water in the room temperature phosphorescent material will affect its luminescence performance, especially the phosphorescence. The more water content in the room temperature phosphorescent material, the weaker its phosphorescence intensity. This is also one of the reasons why the room temperature phosphorescent material of the present invention can be used as a humidity sensor element.

[0144] In summary, the present invention adopts nitrogen-doped or nitrogen-metal ion-doped carbon quantum dots as the main phosphorescent color-emitting center, and uses a double network of polyacrylamide and cellulose-based derivatives as a substrate and a secondary phosphorescent color-emitting center. The room temperature phosphorescent material prepared by UV curing, cross-linking and further dehydration shows different visible light colors under the excitation of two wavelengths of ultraviolet light, and the color is tunable. It can be applied to anti-counterfeiting inks, optical information coding, optoelectronic devices, advanced information encryption and humidity sensing detection and other fields, and has broad promotion and application prospects.

[0145] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.

Claims

1. A UV-curable color-tunable dual-emission room temperature phosphorescent material, characterized in that: The raw materials including carbon quantum dots, acrylamide and cellulose-based derivatives are mixed, heated, cross-linked and dried by UV curing to obtain a UV-cured color-tunable dual-emission room temperature phosphorescent material; The carbon quantum dots are nitrogen-doped carbon quantum dots or nitrogen-metal ion-doped carbon quantum dots.

2. The UV-curable color-tunable dual-emission room temperature phosphorescent material according to claim 1, characterized in that: The cellulose-based derivative is one or more of cellulose nitrate, cellulose acetate, cellulose acetate butyrate, cellulose xanthate, methyl cellulose, carboxymethyl cellulose, ethyl cellulose, hydroxyethyl cellulose, cyanoethyl cellulose, hydroxypropyl cellulose and hydroxypropyl methyl cellulose.

3. The UV-curable color-tunable dual-emission room temperature phosphorescent material according to claim 1, characterized in that: The method for preparing carbon quantum dots comprises the following steps: (1) Ethylenediaminetetraacetic acid disodium salt and metal salt are mixed evenly in water, heated at 50-95°C until the water is completely volatilized, and then transferred to 60-90°C for further drying to obtain a precursor powder; (2) reacting the precursor powder at 200-400 °C to obtain a reaction product; (3) Dissolving the reaction product and mixing it evenly with an organic solvent, filtering it, and drying the filtrate to obtain carbon quantum dot powder.

4. The UV-curable color-tunable dual-emission room temperature phosphorescent material according to claim 3, characterized in that: The molar ratio of the disodium salt of ethylenediaminetetraacetic acid to the metal salt is 10:(0-10).

5. The UV-curable color-tunable dual-emission room temperature phosphorescent material according to claim 3, characterized in that: The metal salt is selected from one or more of chloride salts of magnesium, calcium, manganese, iron, ferrous iron, cobalt, nickel, copper, zinc ions and hydrates of chloride salts.

6. A method for preparing a UV-curable color-tunable dual-emission room temperature phosphorescent material, characterized in that: The following steps are involved: S1. Add acrylamide, cellulose-based derivatives, photoinitiator, and crosslinking agent to an aqueous solution of carbon quantum dots, and heat to 60-90° C. to obtain a color-tunable dual-emission room temperature phosphorescent material precursor solution; S2. Curing the color-tunable dual-emission room temperature phosphorescent material precursor solution under UV until the precursor solution becomes a non-sticky, non-flowing solid, and drying until the moisture in the solid completely disappears and becomes a hard solid, thereby obtaining a UV-cured color-tunable dual-emission room temperature phosphorescent material.

7. The method for preparing a UV-curable color-tunable dual-emission room temperature phosphorescent material according to claim 6, characterized in that: The mass ratio of the acrylamide, the cellulose-based derivative, the photoinitiator and the cross-linking agent is 100:(0.01-3):(0.1-1):(0.01-1).

8. The method for preparing a UV-curable color-tunable dual-emission room temperature phosphorescent material according to claim 6, characterized in that: The mass ratio of acrylamide to carbon quantum dots is 3000:(0.5-10).

9. Use of the UV-curable color-tunable dual-emission room temperature phosphorescent material according to any one of claims 1 to 5 or the UV-curable color-tunable dual-emission room temperature phosphorescent material prepared by the method according to any one of claims 6 to 8, characterized in that: The UV-curable color-tunable dual-emission room-temperature phosphorescent material is used as anti-counterfeiting ink, characteristic luminescent material for optical information encoding, surface color material for optoelectronic devices, advanced intelligent coating material for advanced information encryption, raw material for phosphorescent objects and appliances, or humidity sensitive element for humidity sensing detection device.

Citation Information

Patent Citations

  • Dual-emission fluorescent molecularly imprinted polymer nanoparticles and preparation method and application thereof

    CN109370565A

  • Carbonized polymer point with adjustable room-temperature phosphorescence lifetime and wavelength, and preparation method and application thereof

    CN111848865A

  • Full-color room-temperature phosphorescent carbon dot under ultraviolet excitation and composition thereof

    CN113201333A

  • Full-color room-temperature phosphorescent carbon dots under visible light excitation and composition thereof

    CN113214827A

  • Preparation method of oxygen-doped dual-emission carbon dots and application of oxygen-doped dual-emission carbon dots in detection of hydroxyl radicals

    CN118895126A